Tetrastigma hookeri (Laws.) Planch. (Vitaceae), a new addition to the flora of Vietnam - Cuong, Nguyen The (Academia Journal of Biology, 2014)
The largest genus of Vitaceae in the flora of Vietnam is Tetrastigma (Miq.) Planch., which has been known to comprise 39 species, 11 endemic species. Distribution of T. hookeri (Laws.) Planch. has been known in India, Burma, Thailand, Indonesia and Malaysia but it has not been known in Vietnam. During the study of Tetrastigma specimens and documentations in herbaria, we have found that T. hookeri (Laws.) Planch. has distributed also in Vietnam, with specimens collected in the Kon Tum province. The specimens of voucher are kept in Hanoi Herbarium, Institute of Ecology and Biological resources, Hanoi (HN). This species is closely related to T. lanceolarium (Roxb.) Planch. but differs in the characters of the leaves, berries and seeds. This was a new species for the flora of Vietnam.